SEXTORTION: TANTANGAN SOSIAL DAN HUKUM DALAM KEJAHATAN SEKSUAL BERBASIS CYBERCRIME - Silmiwati (Fakultas Hukum Universitas Bangka Belitung, 2026)
Sextortion as a form of contemporary crime that exploits digital space as a means of sexual extortion, examining three main aspects: perpetrators' modus operandi, the psychological and social impacts on victims, and law enforcement in Indonesia. Using a normative juridical approach and international academic literature review, the study finds that sextortion is carried out through various methods—including emotional manipulation in intimate relationships, grooming of minors, computer hacking, and transnational organized cybercrime—causing severe consequences for victims including profound psychological trauma (anxiety, PTSD, depression, and suicidal risk), social stigma, isolation, and economic and career harm. In terms of legal enforcement, Indonesia lacks explicit regulation categorizing sextortion as a specific criminal offense, relying instead on scattered legal instruments such as the Electronic Information and Transactions Law, Anti-Pornography Law, Penal Code, Child Protection Law, and Sexual Violence Crime Law, resulting in inadequate victim protection, low reporting rates due to social stigma, and limited digital forensic capacity among law enforcement; therefore, a comprehensive approach is needed encompassing regulatory reform, victim-centered and trauma-informed justice principles, capacity building for law enforcement, and cross-sector collaboration among government, digital platforms, and civil society.